THE FUTURE OF DIGITAL BANKING IN UZBEKISTAN: LESSONS FROM THE US AND ADOPTION IN UZBEKISTAN’S BANK SPHERE (Conferencea, 2024)
This article aims to understand the complexities of banking innovation in the digital economy. It will build a theoretical framework using established theories and then explore practical aspects through case studies. The research will ultimately provide insights and recommendations to help banks, policymakers, and researchers drive innovation and growth in the digital age.